Chemogenetic tools and genetic biosensors in redox biology: Probing Hyper7 signals in specific cellular locales - Altun, Hamza Yusuf; Erdoğan, Yusuf Ceyhun; Seçilmiş, Melike; Eroğlu, Emrah (Elsevier Science Inc., 2023)
H2O2 is one of the most studied reactive oxygen species (ROS) in redox biology because of its critical role in oxidant-dependent signaling pathways. Conventional approaches apply exogenous H2O2 on cells and tissues, which barely recapitulates intracellular redox signaling events. An alternative approach is D-amino acid oxidase (DAAO)-based chemogenetic tools that permit intracellular H2O2 generation by D-amino acid catalysis. Exploiting the targetability of the DAAOs to cellular ultralocales allow precise manipulation of the redox tone with high spatial and temporal resolution. DAAOs have been utilized in several redox studies, yet due to the incomplete characterization and the lack of fine-tuned protocol on how to employ DAAOs, the potential of this multiparametric imaging technology could not be fully exploited. Using the ultra-sensitive genetically encoded H2O2 biosensor (HyPer), we tested the performance of a modified version of DAAO (mDAAO) under hypoxic and hyperoxic conditions. Our multiparametric imaging approach unveiled that cell type, cellular locales, pericellular oxygen concentrations, D-amino acid type, and its concentrations are critical and modulatable factors that permit fine-tuned H2O2 generation with high precision. These findings and fine-tuned protocols provide practical approaches for redox scientists to spatiotemporally control oxidative stress-dependent signaling pathways in different cultured cell model systems.
Keywords: Hydrogen Peroxide; Chemogenetics; Genetically Encoded Biosensors